P26 In situ simulation; the ASPiH standards in practice. (November 2018) - Jackson, Louisa; Suggitt, Debbie; Baxter, David; Jafar, Wisam
Abstract : Introduction: Simulation is a powerful tool for learning, and has been shown to be effective for a wide range of skills. In situ simulation (ISS) is delivered in the clinical setting with the objective of incorporating simulated learning into real working environments. This provides additional scope for learning, not only team working and clinical skills, but also in identifying latent errors (Rosen 2012). We established an ISS programme across our Gastroenterology, Acute Medicine and Paediatric departments. This was underpinned by the recent key standards published by the Association for Simulated Practice in Healthcare (ASPiH): clearly defined learning objectives, authentic delivery and faculty proficient in simulation based education (ASPiH 2016). Methods: We identified key learning objectives for each scenario, focusing on human factors (at an individual, team and organisational level) and clinical competencies pertinent to each specialty. Appropriately accredited faculty ran fourteen sessions over a six month period, involving sixty nine members of multi-disciplinary teams. Following each ISS we facilitated a short structured debrief session adapting the SHARP five step approach, highlighting key learning points, providing feedback and enabling reflection (Imperial College 2010). Results: Sixty eight of our sixty nine participants reported enjoying the simulation by the end of the session. 91% stated being involved would help their further practice and 96% felt better prepared for a similar real life clinical scenario. Importantly all team members felt well supported during the debrief process. Through our sessions we recognised both latent error and resource requirements. Conclusions: In conclusion, ISS has proved a useful modality to deliver teaching in the clinical setting and the response from across the multi-disciplinary teams has been overwhelmingly positive. In addition to acting on identified latent errors, we are now working alongside senior nursing colleagues to embed these actions locally. We have highlighted specific teaching needs and established mandatory teaching days for our Junior and Senior Clinical Fellows. Our team is currently expanding our ISS programme; July will be our ISS takeover month where the faculty will engage and support clinical teams across the hospital through simulation teaching. References: Association for Simulation Practice in Healthcare. Simulation-based education in healthcare. Standards framework and guidance 2016. Available from http://aspih.org.uk/wp-content/uploads/2017/07/standards-framework.pdf [Accessed: 28 May]. The London Handbook for Debriefing: Enhancing performance debriefing in clinical and simulated settings 2010. Imperial College London. Available at https://emergencypedia.files.wordpress.com/2014/03/london-debriefing.pdf [Accessed: 22 May 2018]. Rosen MA, Hunt EA, Pronovost PJ, Federowicz MA, Weaver SJ. In situ simulation in continuing education for the health care professions: A systematic review. Journal of Continuing Education in the Health Professions2012;32(4):243–54.